The occurrence of defects in the lower limbs in children with polyarticular hypermobility - Roszak, Magdalena; Weber-Nowakowska, Katarzyna (Journal of Education, Health and Sport, 2018)
Introduction. Faulty posture, overweight and obesity are one of the most common health problems in Poland among children and adolescents. Although posture disorders are usually commonly diagnosed, the occurrence of polyarticular hypermobility is rarely taken into account when planning corrective exercises. The aim of the study was to assess the influence of hypermobility on the occurrence of lower limb defects. Materials and methods. The study included 35 children (14 girls and 21 boys) aged 6-10 years with diagnosed in a Beighton test hypermobility . The control group also consisted of 35 children of the same age and the same number of girls and boys. Using the calipers and the goniometer, the valgus, varus or hyperextension of the knee joints, valgus and varus of the ankles as well as flat feet have been assessed. Then, the results obtained in the hypermobility and control group were compared. Results. There were statistically significant differences (p = 0.001) in the occurrence of most defects of the lower limbs in children with hypermobility in relation to healthy ones. For knee valgus, the rho-Spearman correlation was r = 0.611; for deformity of the knees r = 0.56; for knee hyperextension r = 0.52; for flat feet r = 0.628; for valgity of feet r = 0.555. In the examined groups, no varus deformation was observed. Conclusions.1.Hypermobility predisposes to the occurrence of lower limb defects in children. 2. There is an indication for performing screening tests in children of early school age and implementation of prevention programs for polyarthritis hypermobility.